2017
DOI: 10.29050/harranziraat.321116
|View full text |Cite
|
Sign up to set email alerts
|

Pleurotus ostreatus Mantarının Cips Üretiminde Kullanımı

Abstract: ÖzBu çalışmada atıştırmalık ürün sektöründe önde gelen cipsin istiridye mantarı tozu ile zenginleştirilmesi amaçlanmıştır. Üretimde kullanılacak hammaddelerin oranları ve pişirme parametreleri Yanıt Yüzey Yöntemi (YYY) esas alınarak denenmiştir. Üretilen cips örneklerinin, fizikokimyasal (kuru madde, kül, protein, su aktivitesi, yağ) ve duyusal analizleri sonuçlarına göre, mantar tozu oranı (MTO), kızartma süre ve sıcaklığı YYY ile optimize edilmiştir. Kızartılmış mantar cipsleri için optimum pişirme koşulları… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…(2021) determined that the dry matter content of freshly harvested Lactarius deliciosus mushroom species, known as ‘kanlıca’ in Turkish, was 12.22% and the pH value was 6.51. Doğan (2016) determined the dry matter content of fresh oyster mushrooms used as raw material to be 10.45% and pH value of 5.95. Roncero‐Ramos et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2021) determined that the dry matter content of freshly harvested Lactarius deliciosus mushroom species, known as ‘kanlıca’ in Turkish, was 12.22% and the pH value was 6.51. Doğan (2016) determined the dry matter content of fresh oyster mushrooms used as raw material to be 10.45% and pH value of 5.95. Roncero‐Ramos et al .…”
Section: Resultsmentioning
confidence: 99%
“…(2004) reported that the dry matter contents of fresh mushrooms of Agrocybe aegerita and P. eryngii species were 12.6% and 13.4%, respectively, and when subjected to a 10‐min grilling process, the dry matter contents of the mushrooms were reported as 15.4% and 17.9%, respectively. Doğan (2016) determined the dry matter content of fresh oyster mushrooms used as raw material to be 10.45% and emphasised the significant role of compost formulation in affecting the physical, chemical, and biochemical properties of mushrooms. In this context, El Sebaaly et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ali gibi baktıklarını ifade eder 352 . İzzettin Doğan, Atatürk'ün Alevi İslam anlayışını kabul edenler açısından büyük bir kurtarıcı olduğunu belirtir 353 . _____…”
Section: J Atatürkunclassified
“…Pleurotus species have a great potential to produce novel value-added products (Wakchaure et al, 2010). The incorporation of dried cultivated P. ostreatus into processed foods such as wheat bread (Ndung'u et al, 2015;Oyetayo and Oyedeji, 2018), yoghurt (Pelaes et al, 2015), meatball (Süfer et al, 2016), and chips (Doğan et al, 2017) as an additive has been reported to enhance sensory, nutritional, nutraceutical or functional characteristics, in addition, the bioactive compound bioavailability of the products enriched with P. ostreatus was studied (Regula et al, 2016). In recent years, some dietary supplements derived from P. ostreatus have also been produced and these are commercially available in the market (Reis et al, 2017;Bulam et al, 2018;Üstün et al, 2018).…”
Section: Introductionmentioning
confidence: 99%